TINJAUAN YURIDIS TERHADAP PENDAFTARAN MEREK CITAYAM FASHION WEEK MENURUT UNDANG-UNDANG MEREK & INDIKASI GEOGRAFIS - Rodrigo, Valencia Rodrigo; Thomas Abbon; Edward ML Panjaitan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The registration of the rights to the Citayam Fashion Week brand by famous artist XXXX sparked a public reaction that considered it immoral, because he was not the one who popularized the Citayam Fashion Week brand. The purpose of this study is to examine who has the right to the Citayam Fashion Week brand according to law number 20 of 2016 concerning trademarks and geographical indications, and whether the registration carried out by XXXX is in accordance with the provisions of the First To File system in trademark registration regulated in the Trademark Law. The research method used in this study is normative juridical, namely research by examining the sources of primary, secondary and tertiary legal materials. The results of the author’s research are based on the Trademark Law, subjects entitled to trademarks are subjects who first registered trademark rights with the Ministry of Justice and Human Rights.XXXX’s actions in registering the Citayam Fashion Week mark are in accordance with the provisions of the first registrant system or First To File, and do not violate the provisions concerning marks that cannot be registered and rejected as stipulated in Law Number 20 of 2016 on Marks and Geographical Indications, and therefore XXXX has the right to register the Citayam Fashion Week brand.